2017
DOI: 10.1212/nxi.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction in patients with primary progressive MS

Abstract: Objective:We tested the hypothesis that olfactory function is more impaired in patients with primary progressive MS (PPMS) than that in relapsing-remitting MS (RRMS).Methods:Standardized olfactory testing was performed in 32 patients with PPMS, 32 patients with RRMS, and 32 healthy controls (HCs). Patients with olfactory dysfunction due to an alternative primary etiology were excluded. The validated olfactory testing method yielded individual scores for olfactory threshold, odor discrimination, and odor identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…It is notable to mention that this was one of the few studies where the Threshold Discrimination Identification (TDI) test was performed as the screening tool. (20) So far, existing data suggest that MS patients are at an elevated risk of experiencing olfactory dysfunction. Moreover, our subgroup analysis showed that the pooled prevalence of olfactory dysfunction in studies whose mean EDSS was more than 3 was higher compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable to mention that this was one of the few studies where the Threshold Discrimination Identification (TDI) test was performed as the screening tool. (20) So far, existing data suggest that MS patients are at an elevated risk of experiencing olfactory dysfunction. Moreover, our subgroup analysis showed that the pooled prevalence of olfactory dysfunction in studies whose mean EDSS was more than 3 was higher compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bei 15-20 % der Betroffenen (meist ältere Patienten > 40 Jahre) beginnt die Erkrankung als primär chronisch-progrediente MS (Primary Progressive MS = PPMS) mit einer schleichenden Gangverschlechterung durch eine progrediente spastische Paraparese [24]. Diese Symptomatik wird leider oft jahrelang fehldiagnostiziert, da viele Betroffene wegen vermuteter Rückenleiden oder lumbaler Bandscheibenvorfälle behandelt werden.…”
Section: Verlaufunclassified
“…Impairment of olfactory function is a characteristic feature in MS with different modalities reflecting different aspects of MS pathology. [1][2][3][4][5][6][7][8] The capacity to correctly identify odours (identification) and to discriminate them (discrimination) is affected in MS patients displaying both clinical and paraclinical signs of MS-associated neurodegeneration such as physical or cognitive disability progression, brain atrophy and reduced retinal thickness. 5,6,9 On the other hand, olfactory threshold is transiently impaired in active MS and during acute relapse resolving in phases of clinical stability, which indicates an association with short-term inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%